Drivers of behaviors: How do city pilots shape residential energy-related emissions through perceptions? - Xing, Hua; Li, Xiangyang (Frontiers in Psychology, 2023)
Residential energy consumption, as a major source of emissions in cities, is also a policy priority for the construction of low-carbon cities. The occurrence of residential energy saving and emissions mitigation behaviors is closely related to low-carbon perceptions. Against this background, cities make efforts to shape residential low-carbon perceptions. In order to investigate residential energy consumption and carbon emissions, this study takes low-carbon city pilots as the policy context and establishes the difference-in-difference model on Chinese prefecture-level cities. Theory of planned behavior is utilized to analyze the influence mechanism of residential low-carbon perceptions. Results indicated that (1) low-carbon city pilots can decrease residential energy-related emissions and pass a variety of robustness tests. Multiple pilot eligibility and policy lag would reinforce policy effects. (2) Mechanism analysis shows that low-carbon city pilots can strengthen residential behavioral attitudes, establish subjective norms, and adjust perceived behavioral control. All three mechanisms together shape residential low-carbon perceptions, which consequently promote energy-related emissions mitigation behaviors. (3) Due to differences in geographic location and city size, there is heterogeneity for the policy effects of low-carbon city pilots. For the future research, it is necessary to expand the scope of residential energy-related emissions, find out the potential influencing factors, and track the policy effects in long-term.